Tracking Physical Literacy in Aotearoa New Zealand: concerns of narrowed curriculum and colonisation. Issue 2 (4th May 2021) - Stevens, Susannah Ruth; Ovens, Alan; Hapeta, Jeremy William; Petrie, Kirsten
ABSTRACT: The concept of physical literacy (PL) has increasingly drawn global interest from practitioners, academics and policymakers within the fields of sport, health and physical education. Its value and appeal appear to lie in its potential to help refocus attention on the importance of human physicality and movement in enabling individuals to flourish and lead fulfilling lives Whitehead, M. (Ed.). (2010). Physical literacy: Through the life-course. International studies in physical education and youth sport . Routledge. In this sense, it overlaps with the aims of physical education (PE) and has increasingly been seen as having an influence on future curriculum development in many Western countries. In our view, there is a need to critically question this influence, particularly in the sense that the concept is not just redefining the nomenclature of the subject area; but also its nature, focus and outcomes. This need to critically question has also become more prevalent as neoliberal technocratic agendas have pushed for clearer measures of the impact associated with government expenditure, increased individual responsibility for health outcomes and the subsequent development of measurement tools and standards. The concern here, particularly for a country like Aotearoa New Zealand, is that the current curriculum risks becoming colonised by a concept, that fails to adequately address its national values, cultural identity and broad educative aspirations.